Continuous lattices and domains - Gierz, Gerhard (Encyclopedia of mathematics and its applications, 2003)
Information content and programming semantics are just two of the applications of the mathematical concepts of order, continuity and domains. This authoritative and comprehensive account of the subject will be an essential handbook for all those working in the area.